Biochemical Markers and Physiological Dysregulation Associated with Sleep Deprivation: A Systematic Review: Biochemical Markers and Physiological Dysregulation Associated with Sleep Deprivation - Khan, Sara Yar; Inayat, Bela; Ihsan, Khushboo; Aziz, Asma; Fida, Najma; Muhammad, Gul (Pakistan Journal of Health Sciences, 2026)
Sleep deprivation has become increasingly common in modern society and is associated with various adverse health outcomes. Evidence suggests that inadequate sleep may disrupt biochemical regulation and contribute to systemic physiological disturbances. Objectives: To synthesize current evidence on biochemical markers and physiological dysregulation associated with sleep deprivation in adult populations. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A literature search was conducted in PubMed, Scopus, and the Cochrane Library for studies published between January 2017 and March 2024. Original human studies reporting biochemical or physiological outcomes related to sleep deprivation or sleep restriction were included. Titles and abstracts were screened, followed by full-text evaluation. Data on study characteristics, sleep assessment methods, and outcomes were extracted. Study quality was assessed using the National Institutes of Health Quality Assessment Tool. Due to heterogeneity across studies, findings were synthesized narratively. Results: Fourteen studies met the inclusion criteria. The evidence consistently showed that sleep deprivation is associated with neuroendocrine stress activation, metabolic disturbances, inflammatory responses, and oxidative stress. Increased cortisol levels, impaired glucose metabolism, elevated inflammatory markers such as C-reactive protein and interleukin-6, and increased oxidative stress markers were commonly reported. Physiological consequences included cardiovascular strain, autonomic imbalance, cognitive impairment, mood disturbances, and reduced immune function. Conclusions: Sleep deprivation is associated with significant biochemical alterations and multi-system physiological dysregulation. Adequate sleep duration and quality appear to be important modifiable determinants of cardiometabolic and neuroimmune health.